A Mini Review of the Preparation and Photocatalytic Properties of Two-Dimensional Materials - Hao, Shuhua; Zhao, Xinpei; Cheng, Qiyang; Xing, Yupeng; Ma, Wenxuan; Wang, Xiaoke; Zhao, Gang; Xu, Xijin (Frontiers in Chemistry, 2020)
The successful preparation and application of graphene shows that it is feasible for the materials of single atom or few atomic layers thickness to exist stability in nature. And these materials can exhibit unusual physical and chemical properties due to their special dimension effects. At present, researchers have made great achievements in the preparation, characterization, modification, and theoretical research of 2D materials. Because the structure of 2D materials is often similar, it has a certain degree of qualitative versatility. Besides, 2D materials often carry good catalytic performance on account of their more active sites and adjustable harmonic electronic structure. In this review, taking 2D materials as examples (graphene, boron nitride (h-BN) and transition metal sulfide and so on), we review the crystal structure and preparation methods of these materials in recent years, focus on their photocatalyst properties (carbon dioxide reduction and hydrogen production), and discuss their applications and development prospects in the future.